2016
DOI: 10.3390/toxins8120354
|View full text |Cite
|
Sign up to set email alerts
|

Growth-Phase Sterigmatocystin Formation on Lactose Is Mediated via Low Specific Growth Rates in Aspergillus nidulans

Abstract: Seed contamination with polyketide mycotoxins such as sterigmatocystin (ST) produced by Aspergilli is a worldwide issue. The ST biosynthetic pathway is well-characterized in A. nidulans, but regulatory aspects related to the carbon source are still enigmatic. This is particularly true for lactose, inasmuch as some ST production mutant strains still synthesize ST on lactose but not on other carbon substrates. Here, kinetic data revealed that on d-glucose, ST forms only after the sugar is depleted from the mediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…In a previous publication [ 21 ], we demonstrated that ST formation only occurs at low specific growth rates. Consequently, in a medium with d -glucose as the growth substrate, ST production occurs only after carbon source exhaustion, during the late stationary phase of growth.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…In a previous publication [ 21 ], we demonstrated that ST formation only occurs at low specific growth rates. Consequently, in a medium with d -glucose as the growth substrate, ST production occurs only after carbon source exhaustion, during the late stationary phase of growth.…”
Section: Resultsmentioning
confidence: 58%
“…The velvet protein was present in the nuclei both in the light and in the darkness at the tested glucose concentrations between 1 and 2%. In our experience, using the medium and growth conditions set out in Németh et al [ 21 ], a velvet wild-type strain produced over twice as much ST when grown in the dark, regardless of whether the cultivation was on agar plates or in fermenters. Our results with the aodA mutant backgrounds imply that a basal level production under illumination (“stage 1”) is essentially unchanged regardless of the absence or presence of AOX, or its exact amount; that is, it seems irresponsive to the ratio of the alternative/total respiration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated that among naturally occurring microorganisms, strain RS1911 had a relatively high ability to ferment lactose. Although lactase (β-galactosidase) from ascomycete fungi, such as the genus Aspergillus or Penicillium, are well known [15,[34][35][36][37], little information is available for basidiomycete fungi. Lactose does not exist in regular mushroom habitats in the first place, so it is presumed that lactase is not particularly necessary for growth.…”
Section: Effect Of the Lactose Concentration On Fermentationmentioning
confidence: 99%
“…fumigatus (Fréalle et al 2013 ). A role of LaeA in oxidative stress response would be in agreement with its essential role in fungal sporulation (Bayram and Braus 2012 ), its necessity for extracellular enzyme production (Karimi-Aghcheh et al 2014 ), and requirement for secondary metabolite production (Németh et al 2016 ). Since both citric and itaconic acid require high oxygen tensions for their accumulation, they are very likely under oxidative stress, although this has never been experimentally investigated so far.…”
Section: Regulation Of Citric Acid and Itaconic Acid Accumulation By mentioning
confidence: 82%